The importance of Hindeodus parvus (Conodonta) for the definition of the Permian-Triassic boundary and evaluation of the proposed sections for a global stratotype section and point (GSSP) for the base of the Triassic - Yurij D. Zakharov; Cheng-yuan Wang; Anton Ramovš; Heinz W. Kozur (Geological Survey of Slovenia, 1995)
The biostratigraphic Permian/Triassic (P/T) boundary is defined by the first appearance of H. parvus. The first appearance of H. parvus within the dine H. latidentatus-H. parvus is a globally recognizable event in the conodont evolution.The first appearance of H. parvus is not facies related and can be observed both in ammonoid-free shallow-water deposits and in ammonoid-bearing pelagic deposits. H. parvus is a common, easily determinable species known so far from the entire Tethys, Japan, western North America, Boreal realm (Greenland)and the Tethyan margin of Gondwana. H. parvus is the first species withworld-wide distribution to appear after the absolute minimum in the faunal diversity indicated by the minimum in The Meishan section (South China) contains a continuous, pelagic sedimentaryrecord across the P/T boundary without stratigraphie gaps. It is nearly unaltered thermally (CAI = 1-1.5). Its fossil content (ammonoids, conodonts, foraminifers,bivalves, brachiopods, sporomorphs etc.) and event succession have been thoroughlystudied. Absolute age and magnetostratigraphy have also been subjected to intensive studies. The section is readily accessible and under protection of the government. This section is best suitable as a global stratotype section and point (GSSP) for the base of the Triassic. No other section in the world is known tobe qualified for defining the P/T boundary in a GSSP. H. parvus made its earliest appearence in the middle part of Boundary Bed 2 (Bed 27) at Meishan. It evolved within Bed 27 from H. latidentatus within a phylomorphogenetic continuum in a continuous and monofacial stratum. The biostratigraphic P/T boundary lies very close to the event boundary (15 cm above the event boundary at the baseof Boundary Bed 1 = Bed 25, and a few centimetres above the minimum in Ô'13C in the lower Boundary Bed 2).